Application of fuzzy modeling to identify the hydrothermal alterations in the Ramand region of Qazvin - Saeed Abbaszadeh; Bijan Maleki; Seyed Reza Mehrnia; Saeedeh Senemari (Journal of Economic Geology, 2018)
Introduction Complete recognition of exploration criteria is considered as an important step in the systematic and scientific analysis of mineral potential mapping. The starting point of this analysis is recognition of the mineral potentials and the mechanism of their formation in different geological areas. In order to achieve such goals we can benefit from the known mineralization information. Integrating and analyzing all the data in the geographic information systems (GIS) can lead to the identification of promising mineral areas for future studies (San Soleimani et al., 2011). GIS can be used to organize, process, analyze and integrate the results of geological, geochemical and geophysical, tectonic and alteration studies in order to identify and evaluate the potential of different minerals (Bonham Carter, 1998). The aim of this paper is to apply the fuzzy integration method in GIS with using all the information, without the need to simplify them, in less time and with acceptable accuracy in order to recognize mineral potentials in the Ramand region. Investigation of mineral potentials in this area with using fuzzy logic in addition to the scientific-research aspects, can provide the discovery of appropriate patterns for other mineral resources in Iran.